Assessing the temporal dynamics of Frankliniella schultzei (Thysanoptera: Thripidae) in commercial soybean crops in North Brazil. (14th September 2021) - dos Santos, Juliana L.; Sarmento, Renato A.; Pereira, Poliana S.; Noleto, Luciane R.; Reis, Kayo H. B.; Pires, Warly S.; Peluzio, Joenes M.; Medeiros, Juliana G.; Santos, Abraão A.; Picanço, Marcelo C.
Abstract: Thrips are considered a secondary pest of soybean in Brazil, but high densities have been noticed since the last harvests (2017/18 and 2018/19), yet no study has provided an initial hypothesis regarding the causes of such events. We aimed to identify some of the factors related to Frankliniella schultzei Trybom (Thysanoptera: Thripidae) temporal dynamics in commercial soybean crops located in Tocantins (Northern Brazil). We undertook evaluations during soybean vegetative, flowering, and fruiting stages on 200 plants per field in each sampling date ( n = 22). Our results indicated that the densities of F. schultzei were similar among fields and soybean phenological stages. The density of thrips showed a significant negative relationship with rainfall, but it was not related to either air temperature, photoperiod, relative humidity, or wind speed. The predators' density was less than 170 individuals (summing all assessments), and it was not associated with thrips density. This study indicates rainfall as the leading factor associated with the temporal dynamics of F. schultzei in commercial soybean crops.